Does Mediterranean diet correlate with cognitive performance among elderly? A cross-sectional study from Cyprus - Ince, Nezire; Gelener, Pınar; Besler, Halit Tanju (Progress in Nutrition, 2020)
Purpose: Today, the importance of the Mediterranean Diet is emphasized due to its beneficial effects onchronic and neurodegenerative diseases, which represent a serious health problem affecting an increasing number of elderly people. Our objective was to investigate whether MeDi influences cognitive functions in the elderly. Methods: 541 participants over 50 years of age were selected by “Stratified random sampling” method. Adherence to a Mediterranean Diet was measured using MeDi Adherence Screener. Neuropsychological tests were evaluated by Mini Mental State Examination (MMSE) and Subjective Cognitive Complaints Scale (SCC). Anthropometric measurements like body analysis, handgrip strength, waist and mid-upper arm circumference were also assessed. Results: Out of 541 participants, 25.3% had high, 68.4% had medium and 6.3% had low adherence to MeDi. The MMSE scores showed that 79% of the participants were normal, 20% had mild dementia and 1% had severe dementia. The SCC showed that 42% had good, 52% had moderate and 6% had poor subject memory. A weak and positive correlation was found between higher MeDi scores and higher MMSE scores. This correlation was particularly observed in attention-calculation, language and recall. There was a positive correlation between the consumption of canned tuna fish, legumes, dark green leafy vegetables, olives, olive oil and MMSE scores. Additionally age, right hand grip strength and Adherence to MeDi scores were significantly predictors of MMSE scores (p